2000
DOI: 10.1191/026921500666642221
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind placebo-controlled study of botulinum toxin in upper limb spasticity after stroke or head injury

Abstract: Botulinum toxin produced beneficial effects in spasticity and passive range of movement in the hemiplegic upper limb. Increasing the dose increased the magnitude of response for impairments in some muscle groups but had little effect on duration of response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
113
2
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(119 citation statements)
references
References 14 publications
0
113
2
4
Order By: Relevance
“…From the 98 selected papers, six fulfilled all inclusion criteria [8][9][10][11][12][13] . Despite one study 8 presented the described criteria, it was excluded from the metaanalysis because it did not present comparable data to be analysed ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…From the 98 selected papers, six fulfilled all inclusion criteria [8][9][10][11][12][13] . Despite one study 8 presented the described criteria, it was excluded from the metaanalysis because it did not present comparable data to be analysed ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Concealment of treatment allocation was adequate in two trials 11,26 and unclear in the other nine. 7,10,21,[23][24][25][27][28][29] Blinding of patients and of the outcome assessor was poorly reported in four studies. 10,21,27,29 The Ashworth score was used as a primary outcome measure in all trials, but some trials used the scale as a continuous measure, 7,10,11,21,23,24,28 whereas others used it as a categorical measure.…”
Section: Findings Description Of Studiesmentioning
confidence: 99%
“…7,10,21,[23][24][25][27][28][29] Blinding of patients and of the outcome assessor was poorly reported in four studies. 10,21,27,29 The Ashworth score was used as a primary outcome measure in all trials, but some trials used the scale as a continuous measure, 7,10,11,21,23,24,28 whereas others used it as a categorical measure. [25][26][27]29 Overall, 29 (3.7%) patients were excluded by the studies after randomization or loss to follow-up: in one study 21 no indication of allocation (BoNT vs. placebo) was given for two dropouts; in the other trials there were 15 BoNT-treated dropouts and 12 placebo-treated dropouts.…”
Section: Findings Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Different treatment methods have been used for treatment of spasticity include physical therapy, oral anti-spastic drugs, chemical nerve block and motor point block using phenol or ethyl alcohol and botulinum toxin injection [5,6]. It has been reported that muscular injections of botulinum toxin type A decreases muscular tone in hypertonic muscles of the hand, with improvement in the use of the upper limb and a decrease in complications [7][8][9][10]. However, the development of neutralizing antibodies can reduce the efficacy of treatment.…”
mentioning
confidence: 99%